Identification of recombination centers responsible for reduction of energy conversion efficiency in CdTe‐based solar cells. Issue 7 (4th April 2014) - Karczewski, G.; Chusnutdinow, S.; Olender, K.; Wosiński, T.; Wojtowicz, T.
Abstract: In this work we discuss experimental data which can explain reasons for the limited energy conversion efficiencies observed in monocrystalline, thin‐film CdTe‐based solar cells grown molecular beam epitaxy. Two kinds of samples has been investigated and discussed – p‐ and n‐type doped CdTe layers with metallic Schottky barriers and p‐i‐n heterojunctions (p‐ZnTe/i‐CdTe/n‐CdTe solar cells). Both kinds of junctions exhibit strong rectifying properties with the rectifying coefficient exceeding 10 5 at 300 K and +/– 1 V. Photovoltaic properties of the solar cells have been determined by I–V measurements under illumination and by spectral characteristics of photocurrent. Based on the spectral measurements it was found that the p‐ZnTe/i‐CdTe/n‐CdTe diodes are sensitive to illumination within the 550–850 nm wavelength range confirming their applicability for solar energy conversion. I–V characteristics measured at 1‐sun illumination yield relatively low energy conversion efficiencies below 4.9%. In order to determine the origin of the limited efficiency in the CdTe‐based solar cells (theoretical limit for n‐CdTe/p‐ZnTe solar cells is as high as 20%) the deep level transient spectroscopy (DLTS) technique has been applied. The results of these DLTS studies revealed the presence of deep electron and hole traps. The low‐temperature DLTS peaks can be ascribed to the hole traps in the CdTe absorber. The high‐temperature DLTS peak changes its sign depending on the sign of the filling pulses acting as a majority trap for negative filling pulses and minority trap for positive filling pulses. The estimated activation energies of the majority‐ and minority trap level are equal to 0.74–0.78 eV and 1.05 eV, respectively. The sum of these energies is close to the value of the CdTe energy gap, suggesting that this energy level can be assigned to the recombination center present in the CdTe absorber material. Basing on the logarithmic capture kinetics of the traps detected in the high‐temperature region we assign the recombination center to electronic states of extended defects, probably threading dislocations. Very similar DLTS results obtained for CdTe Schottky barriers confirm the conclusion. Thus, we conclude that not the point defects but rather extended defect are responsible for the limited energy conversion efficiency in CdTe‐based solar cells.